Investigation on Machining Characteristics of Banana Fiber and Silicon Carbide Reinforced Polymer Matrix Composites - GOPALAN, Venkatachalam; PRAGASAM, Vignesh; NARAYANASWAMY, Hitesh Byatarayanapura; BALASUBRAMANIAN, Gokula Krishnan; CHINNAIYAN, Pandivelan (Engineering Transactions, 2020)
In this study, machining characteristics of polymer composite consisting of banana fiber and silicon carbide (SiC) as reinforcements and epoxy resin as matrix are investigated. Reinforcement phases consist of raw banana fiber powder sieved to 100 microns size of 1% (w/w) and SiC powder of 1% (w/w). The conventional machining process is carried out on the fabricated composite samples by considering the depth of cut, feed rate and speed as influential parameters. The central composite design (CCD) is used to design the experiment based on response surface methodology (RSM). The analysis of variance (ANOVA) is used to study the influences of the depth of cut, feed rate and the speed on the material removal rate (MRR) and surface roughness. The results reveal that the feed rate is the most influential parameter for minimizing surface roughness and maximizing MRR. It is observed that the feed rate plays an important role in determining the surface roughness and MRR followed by the depth of cut and speed. The optimized parameters for maximum MRR and minimum surface roughness are also obtained.